2016
DOI: 10.1039/c6nj00646a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and magnetic properties of hollow Co2FeAl nanoparticles: the effects of heating rate

Abstract: Magnetic hollow nanoparticles (HNPs) are of particular interest owing to their broad applications including targeted drug delivery and magnetic resonance imaging. Here, hollow Co2FeAl full-Heusler NPs were successfully synthesized using polyethylene glycol polymer as a capping agent, followed by thermal annealing at 700 °C with heating rates ranging between 5 and 15 °C/min. Increasing heating rate up to 15 °C/min decreased the mean particle size, as characterized by scanning and transmission electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…They found that the lattice constant of prepared nanowires was within 1% of the lattice parameter of the bulk system. Hollow CFA NPs were also prepared by using capping agent, namely polyethylene glycol polymer and then annealed at 700 °C with a heating range from 5 to 15 °C per min [26]. They achieved a maximum saturation magnetization of 95 emu/g and Hc of 730 Oe.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the lattice constant of prepared nanowires was within 1% of the lattice parameter of the bulk system. Hollow CFA NPs were also prepared by using capping agent, namely polyethylene glycol polymer and then annealed at 700 °C with a heating range from 5 to 15 °C per min [26]. They achieved a maximum saturation magnetization of 95 emu/g and Hc of 730 Oe.…”
Section: Introductionmentioning
confidence: 99%
“…Sapkota et al synthesized Heusler alloy Co 2 FeAl nanowires by using electrospinning method with the existence of polymer [20]. Almasi-Kashi et al prepared Co 2 FeAl nanoparticles by using co-precipitation method with the existence of polymer [21,22]. Kumar et al prepared Co 2 FeAl nanoparticles by reducing a methanol impregnated mixture of metal salts [23].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the variation behavior of H C as a function of particle size (see figure 11.2 in [19]), decreasing the size of SD NPs is expected to reduce the corresponding H C. Thereby, the aforementioned trends measured in H C may be caused by the 43% decrease (from 112 to 64 nm) and 20% increase (from 64-77 nm) in the mean diameter of the SD FeNi NPs. Nevertheless, it should also be noted that an enhancement in the SP fraction of NPs can reduce the H C obtained from the hysteresis loop measurements [51]. Therefore, the SP fraction of the FeNi NP samples may differ from each other, which will be investigated in the next section using the FORC analysis.…”
Section: Compositional and Structural Characteristicsmentioning
confidence: 99%